Topology optimization of tungsten/copper structures for plasma-facing component applications. (18th June 2019) - Curzadd, Bailey; von Müller, Alexander; Neu, Rudolf; von Toussaint, Udo
Abstract: Tungsten has established itself as the most suitable plasma-facing material for long-term operation in future magnetic-confinement fusion devices, but its properties make it a poor structural material and complicate the manufacturing of complex components. Recent advances in additive-manufacturing (AM) technology have begun to make the production of tungsten components with complex geometry more feasible. The design freedom afforded by AM could be leveraged to produce more resilient plasma-facing components (PFCs). A methodology to optimize the material distribution of composite PFCs was developed to reduce the maximum thermal stress caused by high heat fluxes. Its use was demonstrated for copper-infiltrated AM tungsten (WAM /Cu) structures. Stress reductions of 50%–85% are predicted under nominal load conditions. Optimized designs also reduce stress over a wide range of off-nominal conditions. The resulting optimized structures are composed of a spatially heterogeneous distribution of W and Cu comprising a broad range of composite mixtures. A sample manufacturable component was modelled based on optimization results. Highlights A methodology to optimize the material distribution of composite PFCs was developed to reduce the maximum thermal stress caused by high heat fluxes. Stress reductions of up to 85% compared to a monolithic W block may be feasible with topology optimization techniques. Optimized component designs are effective at reducing stress even over a wide range of off-nominal conditions. Manufacturable components can be designed based on optimization results.